Challenges in Fostering Functional Positions After the Issuance of the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 1 of 2023 - Rizki Indra Kurniawan; Fibria Indriati Dwi Liestiawati (Publikasi Indonesia, 2024)
Human resource development (HR) is one of the development priorities in Indonesia, including human resources in the public sector. Bureaucratic simplification is one of the efforts to reform the bureaucracy to improve the quality of performance, which has an impact on the equalization of echelon 3, echelon 4, and echelon 5 positions into functional positions. Strengthening functional positions in government agencies is also one of the steps to improve the professionalism of Civil Servants (PNS). This research is a descriptive qualitative research, which collects data through literature studies, observations, and interviews. The result of this study is that there are several challenges faced after the issuance of PANRB Ministerial Regulation Number 1 of 2023. The first is that by determining credit scores and drafting performance contracts only involving functional officials with their direct superiors, it is necessary to pay attention to how these two parties can ensure that functional officials have performance targets by their scope. Second, from the side of the functional position coaching agency, it has the task of monitoring and evaluating the agency that uses its functional position. The challenge is that there is no clear mechanism for following up on the results of the monitoring and evaluation. Then the third is how training can be used by coaching agencies to overcome the competency or knowledge gap that occurs.